CO-resistant hydrogenation over noble metal/α-MoC catalyst - Xuan Liang; Xiangxin Jin; Shixiang Yu; Chengyu Li; Chuqiao Song; Guan Sheng; Xuemin Ye; Rui Gao; Lili Lin; Ding Ma (Nature Communications)
Abstract “Hydrogenation by crude H2 - dehydrogenation to produce pure H2” strategy using liquid organic hydrogen carriers (LOHCs) can reduce the cost and shorten the process of hydrogen purification and utilization. The critical challenge is to eliminate catalyst poisoning by CO impurity in crude H2. Here, we develop a Pd/α-MoC catalyst that enables efficient hydrogenation of N-LOHCs under crude hydrogen feeds (CO concentration>5 vol%) below 150 °C, and has an activity 1-2 orders of magnitude higher than that of traditional Pd-based catalysts. The CO-resistant hydrogenation is also successfully conducted in the models of industrial crude H2 including CO, CO2 and CH4. Water, as solvent, contributes greatly to the hydrogenation activity against CO poisoning, since the utilization of low-temperature water gas shift (WGS) reaction. Moreover, the positive-charged Pd species hinder the combination of H* from WGS reaction and suppressed the undesirable H2 formation and release, which explains the substantial improvement in the performance of Pd/α-MoC compared to that of Pt/α-MoC.